THE IMPACT OF BRAND AWARENESS AND BRAND PERCEIVED QUALITY TOWARDS PURCHASE DECISION - Ali Syah Putra; Erina Alimin; Eddy Eddy; Felix Leonardi; Bertha Nerpy Siahaan (Jurnal Ilmiah Hospitality, 2022)
Apple Company is an American multinational corporation headquartered in Cupertino, California that designs, develops, and sells personal computers, computer software and consumer electronics, such as iMac, iPhone and iPad with the brand name “Apple”. In this research, the problem observed is Apple Company failed to get a good portion of market share in Indonesia despite their success worldwide. And the customers in Indonesia tend to feel that the Apple Company charged the price too high for their products. As the result, it influences the purchase decision of customers which tend to switch their choice to another brand. In conducting the research, the writer uses interview, observation and questionnaire in analyzing data. In getting data, the writer distributed the questionnaire to 33 respondents at IB IT&B Campus Medan that are using iPhone by using purposive sampling method. The questions in the questionnaire consists of 12 questions that include brand awareness, brand perceived quality and purchase decision variables. The result of the calculation and its analysis show that brand awareness and brand perceived quality has impact toward the purchase decision as the tcount(t0) > ttable. The use of F-test shows that